Reinterpretation of the Meaning of Angels in Tafsir Al-Manar (Critical Analysis Studies) - Susilo, Susilo (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Among all the six pillars of faith, faith in angels has its own uniqueness, because it is able to invite debate among Muslim scholars, both in terms of substance and existence. Abduh’s interpretation has its own uniqueness because he attempts to carry out a reconstruction related to the concept of angels. This research will further explore the concept of angels in Abduh’s interpretation as well as look at its consequences for aspects of faith. This research is a library research using descriptive-analytical method. The approach used is hermeneutical. In this study, the primary source used was Muhammad Abduh’s interpretation of QS. al-Baqarah: 30-34 written in Tafsir al-Manar. The results of the study show that according to Abduh, the significance of discussing the nature of angels is the wisdom behind the dialogue between God and the angels in the creation of Adam. He interprets angels more as a natural potential (al-quwa al-tabi’iyyah) rather than a person or creature made of light. If angels are interpreted as natural potentials and laws, then this means that humans are given the ability to empower these potentials, as symbolized by the angels’ prostration to Adam. The consequence of this interpretation of the aspect of faith in angels is maximizing the synergy between humans and their natural potential